The Meloidogyne incognita Nuclear Effector MiEFF1 Interacts With Arabidopsis Cytosolic Glyceraldehyde-3-Phosphate Dehydrogenases to Promote Parasitism - Truong, Nhat My; Chen, Yongpan; Mejias, Joffrey; Soulé, Salomé; Mulet, Karine; Jaouannet, Maëlle; Jaubert-Possamai, Stéphanie; Sawa, Shinichiro; Abad, Pierre; Favery, Bruno; Quentin, Michaël (Frontiers in Plant Science, 2021)
Root-knot nematodes are obligate endoparasites that maintain a biotrophic relationship with their hosts over a period of several weeks. They induce the differentiation of root cells into specialised multinucleate hypertrophied feeding cells known as giant cells. Nematode effectors synthesised in the oesophageal glands and injected into the plant tissue through the syringe-like stylet play a key role in giant cell ontogenesis. The Meloidogyne incognita MiEFF1 is one of the rare effectors of phytopathogenic nematodes to have been located in vivo in feeding cells. This effector specifically targets the giant cell nuclei. We investigated the Arabidopsis functions modulated by this effector, by using a yeast two-hybrid approach to identify its host targets. We characterised a universal stress protein (USP) and cytosolic glyceraldehyde-3-phosphate dehydrogenases (GAPCs) as the targets of MiEFF1. We validated the interaction of MiEFF1 with these host targets in the plant cell nucleus, by bimolecular fluorescence complementation (BiFC). A functional analysis with Arabidopsis GUS reporter lines and knockout mutant lines, showed that GAPCs were induced in giant cells and that their non-metabolic functions were required for root-knot nematode infection. These susceptibility factors are potentially interesting targets for the development of new root-knot nematode control strategies.